Badan Arbitrase Syari’ah Nasional (Basyarnas) Menyelesaikan Sengketa Secara Adil dan Cepat - Sanawiah Sanawiah (Anterior Jurnal, 2013)
This study aims to determine the definition, history, legal basis of the National Syari'ah Arbitration Board and the National Syari'ah National Arbitration Board can resolve disputes fairly and quickly; Research methods; the method used is the Normative juridical method considering that this study emphasizes on data scundir namely by studying and reviewing the principles, materials and rules of the positive law which are from the literature in the legislation, data in the study collected through Observation.The results of this study, the settlement through Arbitration is believed to have advantages compared to court lines, but the settlement through Arbitration also still has weaknesses.